2021
DOI: 10.3389/fcvm.2021.766088
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Drug-Coated Balloon Angioplasty vs. Drug-Eluting Stent Implantation for Drug-Eluting Stent Restenosis in the Routine Clinical Practice: A Meta-Analysis of Randomized Controlled Trials

Abstract: Introduction: In-stent restenosis (ISR) remains a challenging issue despite the great advance of drug-eluting stents (DES). In addition, the consensus was lacking regarding the optimal strategy for DES-ISR. Therefore, we aimed to evaluate angiographic and clinical outcomes of the two most effective treatments DES vs. drug-eluting balloon (DCB) for patients with DES-ISR.Methods: This meta-analysis used the data from the randomized controlled trials (RCTs), which were identified by a systematic search in the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In addition, DCB therapy has been shown to have further beneficial effects, such as plaque regression, healing responses, and positive vessel remodeling [ 23 , 24 ]. These effects can offset negative remodeling; however, treatment with DCB is reported to be less effective for ISR of DES than that for bare metal stenting [ 17 , 25 , 26 ]. In the study, patients after DES implantation consisted of 81.3% and 84.7% of the DCB and DES groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DCB therapy has been shown to have further beneficial effects, such as plaque regression, healing responses, and positive vessel remodeling [ 23 , 24 ]. These effects can offset negative remodeling; however, treatment with DCB is reported to be less effective for ISR of DES than that for bare metal stenting [ 17 , 25 , 26 ]. In the study, patients after DES implantation consisted of 81.3% and 84.7% of the DCB and DES groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In an ISR study, authors reported low LLL rates (0.12±0.45 mm) at 6 months, as well as low rates of the need for revascularisation and of safety events at 12 months 26 . Some recent studies have reported DCB treatment to be moderately less effective than repeat everolimuseluting stent (EES) implantation in reducing TLR for patients with coronary DES-ISR at long-term follow-up 27,28 . Still, a "leave nothing behind" strategy remains of great interest, as it has been suggested to be potentially safer regarding the risk of very late stent-associated events, including lower bleeding risk, because of its shorter DAPT regimen compared with DES 29 .…”
Section: Dcb Use In In-stent Restenosismentioning
confidence: 99%
“…In recent years, the rise of drug-coated balloons (DCBs) has revolutionized care, with multiple clinical trials showing superiority over BA in maintaining primary patency and freedom from target lesion revascularization (TLR) [ 1 - 12 ]. Some procedures with longer or multiple target lesions require multiple DCBs for treatment [ 1 - 5 ]. The increasing use of DCBs has gone hand in hand with an increasing body of positive clinical data and has also been supported by favorable reimbursement [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%